Metal‐Organic Frameworks for CO2 Chemical Transformations. Issue 46 (20th October 2016) - He, Hongming; Perman, Jason A.; Zhu, Guangshan; Ma, Shengqian
Abstract : Carbon dioxide (CO2 ), as the primary greenhouse gas in the atmosphere, triggers a series of environmental and energy related problems in the world. Therefore, there is an urgent need to develop multiple methods to capture and convert CO2 into useful chemical products, which can significantly improve the environment and promote sustainable development. Over the past several decades, metal‐organic frameworks (MOFs) have shown outstanding heterogeneous catalytic activity due in part to their high internal surface area and chemical functionalities. These properties and the ability to synthesize MOF platforms allow experiments to test structure‐function relationships for transforming CO2 into useful chemicals. Herein, recent developments are highlighted for MOFs participating as catalysts for the chemical fixation and photochemical reduction of CO2 . Finally, opportunities and challenges facing MOF catalysts are discussed in this ongoing research area. Abstract : CO2 triggers a series of environmental and energy problems as the primary greenhouse gas in our daily life. MOFs (metal‐organic frameworks) are applied as outstanding heterogeneous catalysts for CO2 chemical transformations. A systematic overview of the development of MOF‐based catalysts for CO2 chemical transformations are reviewed, from the first example to the most recent publication.